Evaluation of commercial traits in the accessions of Medicago sativa L. from Asia Minor - N. Yu. Malysheva; N. L. Isaeva; E. A. Gubanova; L. L. Malyshev (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. One of the main tasks of the present-day breeding practice is the development of high-yielding intensive-type fodder crop cultivars for indoor feeding of livestock. Alfalfa, as a productive and high-protein crop, deserves special attention. An offer of new breeding sources would enable breeders to broaden the diversity of alfalfa cultivars. Objective. The present study involved 65 local varieties and wild accessions of alfalfa from Turkey preserved in the VIR collection. Material and methods. Yekaterinino Experiment Station of VIR (Tambov Province) was chosen as the research site. Evaluation of the alfalfa collection was carried out in 2015–2017, using the methods developed at VIR for fodder crop research targeted at such traits as green biomass yield, seed productivity, and leafiness. The cultivar ‘Marusinskaya 425’ was used as the reference. Results and conclusions. In 2015, four accessions were identified as promising for their green matter yield and seed productivity: local varieties k-3373 and k-3378 from Konya Province, k-5992 from Isparta Province, and k-6116 from Sivas Province. In 2016, three accessions exceeded the reference in the yield of green matter, and three accessions had higher seed productivity. Eight accessions surpassed the reference in leafiness. In 2017, only one accession, k-6009 (Kayseri Province), significantly exceeded the reference in green matter yield. Nine accessions were selected for their high seed yield. The maximum seed productivity was observed in the accession k-3379 (Konya). Leafiness was notably higher than the reference’s in 15 accessions. The average for three years shows that none of the accessions credibly surpassed the reference in green matter yield. Four accessions had higher seed productivity than the reference. According to the three-year average, 11 accessions exceeded the reference in leafiness. All in all, in the three years of study, the accessions k-3373, k-3378 and k-3379 (Konya) were selected for high green matter yield and seed productivity. High seed productivity and leafiness, with satisfactory green matter yield, were registered in the accession k-5992 (Isparta). The accession k-6009 (Kayseri) significantly exceeded the reference in green matter yield, but demonstrated low seed productivity and poor leafiness. The place of origin for the identified local accessions had been Central Anatolia, with its continental climate. These accessions are valuable breeding sources with noteworthy commercial traits. Alfalfa from Asia Minor can be recommended for use in breeding practice, targeted at the development of new high-yielding intensive-type cultivars.